Problematika Implementasi Kurikulum Merdeka di Sekolah Dasar - Azzarah, Sevia; Maya, Mutiah Dina; Rizky, Shaqilla; Simare, Fanny A.; Rif’an, Muhammad; Putri, Zahra; Mailani, Elvi; Manjani, Nurhudayah (Indo-MathEdu Intellectuals Journal, 2024)
This study discusses the implementation of the Kurikulum Merdeka in Elementary Schools with a focus on the problems faced. The research method used is qualitative with phenomenological methods. Data collection techniques are carried out by observation, interviews, and documentation. Qualitative data analysis is carried out through three steps, namely data presentation, data condensation, and drawing conclusions or verification. The results highlight obstacles in the implementation of the Independent Curriculum in SD Negeri 060877, especially related to learning planning and the use of technology. Interviews with grade 1 teachers revealed difficulties in developing project-based learning and implementing Kurikulum Merdeka. The evaluation of Kurikulum Merdeka is carried out by the principal without any problems. This research provides an overview of the challenges faced by teachers in adopting the Kurikulum Merdeka in elementary schools